2018
DOI: 10.1016/j.jcms.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Long term effectiveness of electrochemotherapy for the treatment of lower lip squamous cell carcinoma

Abstract: Intravenous bleomycin-based ECT is a safe and effective therapy for SCC of the lower lip. ECT improves the quality-of-life of patients by preserving the function and the aesthetic appearance of the affected area. ECT provides a therapeutic option for elderly and frail patients who, due to their state of health, are not suitable for, or refuse surgical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
9
0
4
Order By: Relevance
“…In this study, we present the results obtained in our series (n = 33) of malignant melanoma metastases and non-melanoma skin cancers of the HN area treated with ECT. Our findings confirm that ECT provides a degree of local control in the HN cancer in accordance with previous experiences (7,8,(12)(13)(14)(15)(16). ECT achieved an overall response in all patients with a complete response rate of 82%, a low toxicity profile and no severe side effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we present the results obtained in our series (n = 33) of malignant melanoma metastases and non-melanoma skin cancers of the HN area treated with ECT. Our findings confirm that ECT provides a degree of local control in the HN cancer in accordance with previous experiences (7,8,(12)(13)(14)(15)(16). ECT achieved an overall response in all patients with a complete response rate of 82%, a low toxicity profile and no severe side effects.…”
Section: Discussionsupporting
confidence: 92%
“…It is effective in previously irradiated areas where chemo-radiation protocols can be inapplicable (10,11). Because of its selectivity towards dividing tumour cells, when treating safety margins to decrease the risk of recurrence, it spares normal healthy tissue that surround the tumour and preserves organ functions (12,13). This is particularly important in BCC with ill-defined borders and when treating skin tumours of central facial areas where extensive surgery can be disfiguring and where there is a high risk of recurrence after excision (14)(15)(16).…”
mentioning
confidence: 99%
“…Table 1 presents the principal findings of ECT treatment in HNC [ 47 , 48 , 59 , 65 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. Although the literature describing HNC do not always make clear whether the cancer location is cutaneous or mucosal, this review will focus on both cutaneous tumors and mucosal tumors (located in, or derived from, a mucosal surface, such as in the oral cavity, pharynx, larynx) in the head and neck region.…”
Section: Current Clinical Application Of Ectmentioning
confidence: 99%
“…Gargiulo et al reported the effectiveness of a single session of ECT with bleomycin in 21 patients with primary or recurrent lower lip SCC as a specific subsite, including three patients treated in the palliative setting and four patients who received surgery following ECT. The OR rate following a single session of ECT was 100%, with CR in 71.4% and PR in 28.6% of patients [ 87 ].…”
Section: Current Clinical Application Of Ectmentioning
confidence: 99%
“…In these patients, ECT may represent a low-invasive option with unique advantages in terms of hospitalization, tissue preservation, and costs [170,180,187] . Some have proposed administering ECT with neoadjuvant and/or curative intent in patients with small size cancers of the lower lip, tongue, and palate [173,188] . Treatment of these tumors is challenging, due to anatomic constraints, and possible side effects.…”
Section: Head and Neck Cancermentioning
confidence: 99%